Pneumonia after Kidney Transplantation in Children - Soojin Hwang; Jiwon Jung; Joo Hoon Lee; Young Seo Park (Korean Society of Pediatric Nephrology, 2020)
Pneumocystis pneumonia (PCP) is a rare disease in healthy people but a potentially fatal opportunistic infection by Pneumocystis jirovecii in immunocompromised patients with organ transplantation. We present three cases of PCP after kidney transplantation in pediatric patients. First case was a 4-year-old boy diagnosed with Denys-Drash syndrome and received living-donor kidney transplantation from his mother at age of 1. Second case was a 19-year-old male, with polycystic kidney disease, who received kidney transplantation from his mother at the age of 18. Third case was a 19-year-old female with chronic kidney disease of unknown etiology, who received kidney transplantation from her father at age of 15. These three patients who were on immunosuppressive therapy and completed of routine PCP prophylaxis for 6 months had presented with cough and dyspnea more than 1 year after transplantation. Chest x-ray all showed diffuse haziness of both lung fields, and bronchoalveolar lavage from bronchoscopy revealed Pneumocystisjirovecii infection. All patients showed clinical resolution with intravenous trimethoprim-sulfamethoxazole (TMP-SMX) therapy for at least 3 weeks and had continued secondary prophylaxis for another 6-12 months. This report suggests that clinicians should have suspicion for the possibilities of opportunistic infection such as PCP after kidney transplantation in children.